Functional traits of polychaetes change between different types of Posidonia oceanica habitats. (November 2022) - Katsiaras, N.; Evagelopoulos, A.; Simboura, N.; Atsalaki, A.; Koutsoubas, D.
Abstract: Meadows of Posidonia oceanica harbor rich biodiversity and ecosystem functions, yet Biological Traits Analysis on the resident benthic communities are lacking. This study aims to provide insight on the functional diversity of polychaetes communities, a dominant benthic group, between the different habitat types of P. oceanica (plain meadow, strips/patches and dead matte), as well as pilot indicators of habitat modification. The results showed how specific traits relate to the different habitat types. Plain meadow was different to strips/patches and dead matte in functional composition, diversity and thus, the ecosystem functions involved. However, an overlap was observed in functional composition between dead matte and living P. oceanica, due to the remaining matte structure. This highlights the importance of the former on ecosystem functioning and the serious consequences of its current exclusion from conservational legislation. In addition, the classification of species to ecosystem engineering types showed interesting potential as an indicator. Highlights: Different Posidonia oceanica habitats were analyzed using Biological Traits Analysis. Specific trait modalities were found to relate to different layers of P. oceanica structure and habitat types. Plain meadow differed to Strips/Patches and Dead Matte in functional composition, diversity and possibly ecosystem functions. Dead Mattes highly contribute to ecosystem functioning but are threatened by lack of a conservational framework. Types of ecosystem engineering showed potential as an indicator of habitat structure modification.